ANALYTICAL BASIS OF CLINICAL LABORATORY DIAGNOSTICS - Yulayeva I.A.,; Yaxshiboyeva D., (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
The laboratory examination of a patient is usually divided into three stages: pre-analytical, analytical and post-analytical. The analytical stage takes place entirely in the laboratory, while the other two stages have a rather significant extra-laboratory component. It is important to realise that, as in any sphere of human activity, mistakes made in clinical diagnostic laboratories are inevitable. The objective of each laboratory is to establish, through a quality assurance system, a robust set of tools to identify errors and to implement targeted interventions to minimise them.